Qandeel e adab Qwaid o insha for class 3 - Saeeda Maqsood (Lahore: Asian Educational Publisher, 2014)
Qandeel-e-Adab Qawaid-o-Insha: Book 3 is an essential Urdu language textbook that focuses on teaching grammar (qawaid) and writing skills (insha) to students. It provides a systematic approach to mastering the rules of Urdu grammar, including sentence structure, punctuation, and vocabulary. The book also emphasizes creative and formal writing techniques, helping students develop their expression and communication skills in Urdu. Through engaging exercises and activities, the textbook encourages students to apply grammar rules practically and enhance their writing abilities. This book is a valuable resource for students aiming to gain a strong command of Urdu language fundamentals and improve their written communication.